2021
DOI: 10.3390/ijerph181910434
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Pain in COVID-19 Survivors Following Mechanical Ventilation

Abstract: COVID-19 has caused a certain proportion of patients to be hospitalized in intensive care units (ICU) and may cause musculoskeletal and neurological deficits following intubation and mechanical ventilation. The aim of this study was to quantify and describe the presence of shoulder pain in patients released from hospitals after suffering COVID-19. Patients with positive Apley tests were sent to a physiatrist for a clinical evaluation, ultrasound and electromyography (EMG). This evaluation was completed with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…Twenty literature reviews were identified2, 12-30 . Of the remaining studies, 31 presented original research 31-61 , 6 were case series 62-67 , 24 were case reports 68-91 , 1 provided a specialist’s opinion 92 , 4 were editorials 93-96 , and 2 were letters to the editor 97,98 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty literature reviews were identified2, 12-30 . Of the remaining studies, 31 presented original research 31-61 , 6 were case series 62-67 , 24 were case reports 68-91 , 1 provided a specialist’s opinion 92 , 4 were editorials 93-96 , and 2 were letters to the editor 97,98 .…”
Section: Resultsmentioning
confidence: 99%
“…We showed that it is possible to implement a national rehabilitation policy that integrates all levels of health care in response to a pandemic in a developing country. Although it is still too early to evaluate the effectiveness of the rehabilitation plan in COVID-19 in Chile, from a scientific point of view, experiences in evaluation and intervention in these patients have been reported, both at the hospital level and in primary care ( 26 , 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several neuromusculoskeletal complications from proning have been reported in the literature. These include peripheral neuropathies affecting the upper and lower limb, 2 , 3 , 4 , 5 the development of multifactorial musculoskeletal shoulder pain 6 and even cervical spine injury. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Several neuromusculoskeletal complications from proning have been reported in the literature. These include peripheral neuropathies affecting the upper and lower limb, [2][3][4][5] the development of multifactorial musculoskeletal shoulder pain 6 and even cervical spine injury. 7 Peripheral nerve and brachial plexus injuries can be devastating and are associated with reduced quality of life, impaired activity participation, persistent pain, and psychological morbidity.…”
Section: Introduction 1| Problem Descriptionmentioning
confidence: 99%